United States of Tara. The second season [videorecording (DVD)] - Cody, Diablo (CBS DVD : Paramount Home Entertainment [distributor], 2010)
Season two starts with a bang. As Tara decides to move on from her past, a sudden neighborhood incident opens the door to her family's shocking secrets. Her alters, some returning and some new, help unravel the mysteries while simultaneously infusing their own chaos into the mix. Meanwhile, the rest of Tara's family explore their own identities as Max hits a boiling point, Marshall questions his sexuality, Kate takes on an online fantasy persona, and Charmaine finds herself in a love triangle.